The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1519-6984.10113
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte quality of tambaqui (Colossoma macropomum) during the reproductive season

Abstract: The study aimed to analyze the Colossoma macropomum reproductive behavior and quality of the female gametes throughout the reproductive season. The experiment was carried out in Pimenta Bueno -Rondônia State (Northern Brazil) during the reproductive season (2010-2011) using 36 females. Each sampling was performed on a 15 ± 5 days interval. Female gametes were collected by stripping and the following analyses were performed: weight of oocytes released (g); productivity index, fertilization and hatching rate. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Nevertheless, Galo et al (2015) and Chellappa et al (1996) obtained fertilization rates of 86.3% and 80%, respectively, in a single spawning of C. macropomum, which are similar to those that resulted in the present experiment. In addition, the hatching rates in the present study (in both the first and second spawnings) were similar to the 89% rate that was observed by Galo et al (2015) in a single spawning of C. macropomum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, Galo et al (2015) and Chellappa et al (1996) obtained fertilization rates of 86.3% and 80%, respectively, in a single spawning of C. macropomum, which are similar to those that resulted in the present experiment. In addition, the hatching rates in the present study (in both the first and second spawnings) were similar to the 89% rate that was observed by Galo et al (2015) in a single spawning of C. macropomum.…”
Section: Discussionsupporting
confidence: 89%
“…The total oocyte weight and production index obtained in both the first and second spawnings were similar to those reported by Souza et al (2018) in a single spawning of C. macropomum. There was a greater total oocyte weight (Galo et al, 2015) and absolute fecundity (Vieira et al, 1999) with females that had greater body weights, but without great changes in production index (ratio between oocyte weight and fish weight), as demonstrated in the study of Galo et al (2015).…”
Section: Discussionmentioning
confidence: 67%
“…Induced reproduction of the tambaqui among kin specimens is not common due to the fish´s high fecundity (GALO et al, 2015). Increase in endogamy may eliminate important allele combinations such as those related to pathogen resistance and adaptability.…”
mentioning
confidence: 99%
“…2011; Giesing et al . 2011) and time of egg collection within the spawning season (Galo et al . 2015) can affect egg quality.…”
Section: Egg Collection and Use Of Thawed Sperm Samplesmentioning
confidence: 99%